Strategy For Integration Of Cultural Value In Management Of Human Resources - Hani Susanto, Setyo; S, Guntur; Andreas N, Djoko; Harefa, Faonaso (UNIVERSITAS PAKUAN, 2025)
The strategy of integrating cultural values in managing human resources in the Ministry of Defense plays a crucial role in increasing organizational effectiveness. This study aims to analyze how cultural values can be integrated into the policy of human resources effectively by considering existing challenges. Using the mixed methods approach, NVivo 12 for qualitative and SEM-PLS 4 analysis to test the variable relationship quantitatively. The results of the NVivo 12 analysis show that the main challenges in the integration of cultural values lie in the sustainability of policies, sanctions, and strengthening regulations. Meanwhile, the SEM-PLS 4 results show that the integration of cultural values in managing human resources is negatively related to the effectiveness of employee performance (O = -0.573, T-statistics = 5.073, p = 0.000). This shows that culture-based policies that are not in harmony with regulations can create ambiguity, reduce discipline, and reduce work motivation. By referring to the two-factor Herzberg and Resource-Based View theories, this research emphasizes the importance of a clear regulatory-based approach in integrating organizational culture. This study fills the previous research gap, which is more focused on the influence of organizational culture in general, by providing specific analysis related to the integration of cultural values in managing human resources in the defense sector.